SEIR MODEL OF DISSEMINATION FALSE INFORMATION ON FACEBOOK - Muhammad Izzat Abdul Radak @ Abdul Razak; Noorzila Sharif; Ku Azlina Ku Akil; Jasmani Bidin (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Dissemination of false information on social media has become a major problem in creating a peaceful community and led to many outrageous behaviours such as racial discrimination and interpersonal discord. Allegations against individuals, misinterpretation of ideologies, and misrepresentation of the conduct of specific individuals are among the various manifestations of false information that have proliferated extensively on the Facebook platform. Thus, this study aims to analyze the dissemination of false information on Facebook using the SEIR model. The data obtained from the selected postings in August 2023 from Info Berita Semasa, Berita Hari Ini Official and Malaysia Buat Apa Hari Ini. The postings have been classified and filtered to ensure the false information being studied. The results show that the false information was viral, and its posting was received by more than half of the group members and only few numbers of group members have realized that the information is fake. Therefore, the administrator in the group should play a vital part in controlling the dissemination of false information. This study will benefit social media controlling association like Malaysian Criminology and Correctional Association to back-pedal the dissemination of false information on Facebook.